Amtsal and Qashas Normative Study: Analysis of Islamic Education Implementation - Ichsan, Yazida; Salsabila, Unik Hanifah; Husna, Difa’ul (Universitas Islam Negeri Alauddin Makassar, 2020)
Amtsal and qashas in the Qur'an can apply as a method and material. The technique uses a systematic way to achieve specific goals - the content as a study discussion or as the theme of the debate in individual learning. The application of amtsal and qashas in the Qur'an would need to use integrating normative tools with several approaches: psychology, linguistics, science, anthropology, sociology as benchmarks in learning. The application of methods in particular operational and operational periods, qashas, and amtsal can be presented as a descriptive narrative that presented with a gripping narration, diction, and vocals that will make students very interested and can take the lessons in question. The development of amtsal and qashas information technology can also modify with socio drama, visual, and video. However, in subsequent events, a child's cognitive development in the conceptual operational phase uses historical, sociological, legal, anthropological, scientific, and technological perspectives, become something that needs to use.